Ctenocheloides boucheti n. sp., a new ghost shrimp from Papua New Guinea (Decapoda, Axiidea, Ctenochelidae) - Poore, Gary C. B. (Zootaxa, 2015)
Ctenocheloides boucheti, the third species in this widespread but rare genus, is described from Papua New Guinea. It differs from the others in having more acute distal lobe on the eyestalk, more prominent distal bifid tooth on the cheliped ischium, longer cheliped fingers, shorter telson and the antennular and antennal peduncles reaching similar lengths.